(untitled) (Third Sector Social Economic Review, 2021)
Consumers widely use mobile shopping applications created within the scope of mobile marketing. In this respect, determining the factors that affect consumers’ continued use of mobile shopping applications will enable companies to develop these applications according to the needs of consumers. This study aims to examine the increasingly widespread mobile shopping phenomenon and the factors that motivate consumers to continue using mobile shopping. For this purpose, this study expands the technology acceptance model (TAM) and comprehensively discusses the factors affecting the intention to continue mobile shopping. Factors enabling the use of mobile shopping are perceived ease of use, perceived usefulness, enjoyment, suitability to lifestyle, trust in applications, and attitude towards mobile shopping. In this context, a questionnaire was applied to 699 consumers. The obtained data were analyzed with the structural equation model using the R program. The factors of perceived ease of use, enjoyment, conformity to lifestyle, trust, and social norms have a significant and positive effect on attitude, but perceived usefulness has no significant effect on attitude. In addition, the attitude towards using mobile shopping applications has a significant and positive effect on the willingness to continue using these applications.